Circulating Dynamics of SARS-CoV-2 Variants between April 2021 and February 2022 in Turkey - Murat Sayan; Ayse Arikan; Murat Isbilen (Canadian Journal of Infectious Diseases and Medical Microbiology)
The diagnosis of new variants and monitoring their potential effects on diagnosis, therapeutics, and vaccines by genomic sequencing is essential to manage global public crises. In the current study, spike-genome next-generation sequencing was generated from 492 SARS-CoV-2 isolates to evaluate the mutations in Turkey from April 2021 to February 2022. The variant analysis was performed using (Coronavirus Antiviral and Resistance Database (CoV-RDB) by Stanford University). We revealed that the lineages Alpha (B.1.1.7), Beta (B.1.351), Delta (B.1.617.2), Eta (B.1.525), variant of interest (VOI), lota (B.1.526), Zeta (P.2), Omicron (B.1.1.529), and Omicron BA.1 (B.1.1.529.1) were in the circulation in Turkey during the given period. The most common lineages were B.1.1.7, B.1.617.2, B.1.1.529, and B.1.1.529.1 SARS-CoV-2 variant circulation in Turkey seems highly heterogenetic; however, quite similar to the global epidemiologic analysis. The existence of globally circulating variants in the same chronological order in Turkey can be a guide for precautions, treatment, and vaccine options to be taken in the future.